New records of the Endangered southern river otter Lontra provocax, with notes on its diet, in threatened wetlands of southern Chile - Norka Fuentes; Aldo Arriagada (Oryx, 2023)
The wetlands inhabited by the southern river otter Lontra provocax in Chile are subject to anthropogenic disturbances. As a result of the modification and destruction of its habitat, caused by loss of riparian vegetation, and other threats, the species is categorized as Endangered on the IUCN Red List. We monitored the river otter and its diet during September 2020–January 2021 in a swamp forest fragment in southern Chile. We obtained evidence of river otter presence from the upper part of the wetland to the confluence with the Bueno River, suggesting inter-population connectivity of the species in an extensive hydrographic basin. Faeces and food remains showed a predominance of native macrocrustaceans, with introduced fish present at lower levels. The detection of the southern river otter in a fragment of threatened swamp forest suggests a low abundance in environmentally degraded freshwater environments. The identification of subpopulations such as the one reported here provides valuable data to support the conservation of the species in threatened wetlands.